A near-infrared BODIPY-based fluorescent probe for the detection of hydrogen sulfide in fetal bovine serum and living cells. Issue 56 (25th May 2016) - Zhang, Jian; Zhou, Junliang; Dong, Xiaochun; Zheng, Xing; Zhao, Weili
Abstract : A near-infrared (NIR) "off–on" fluorescent probe was developed for the detection of H2 S. The new probe possesses a highly selective and sensitive response to H2 S. The probe has low toxicity and was successfully used to detect H2 S in biological serum samples and living cells. Abstract : A near-infrared (NIR) "off–on" fluorescent probeBDP-680 was developed by taking advantage of the Michael addition reaction of unsaturated double bonds in conformationally restricted BODIPY to allow detection of H2 S. The new probe possesses a highly selective and sensitive response to H2 S. Such a NIR probe has been applied successfully to detect H2 S in 10% deproteinized fetal bovine serum (FBS). The detection limit of the probe for NaSH in 10% deproteinized FBS sample was calculated to be about 1 μM which is consistent with the value obtained from serum free solutions (0.5 μM). The probe is of low toxicity and has been successfully used to detect H2 S in living cells.